2003
DOI: 10.1007/s00259-003-1249-3
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography with [18F]FDOPA and [18F]FDG in the imaging of small cell lung carcinoma: preliminary results

Abstract: Small cell lung carcinomas (SCLC) express neuroendocrine markers, and dihydroxyphenylalanine (DOPA) is known to accumulate in neuroendocrine tumours. This study was performed with the aim of evaluating the uptake of 3,4-dihydroxy-6-(18)F-fluoro-phenylalanine ([(18)F]FDOPA) by SCLC, based on comparison with the results of fluorine-18 fluorodeoxyglucose ([(18)F]FDG) positron emission tomography (PET) and standard imaging procedures. [(18)F]FDG PET and [(18)F]FDOPA PET were performed on four patients with newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 11 publications
1
31
1
1
Order By: Relevance
“…This is in line with findings on other aggressive (dedifferentiated?) neuroendocrine tumors, such as small cell lung cancer and metastatic paraganglioma in patients with a SDHB gene mutation, in which 18 F-FDG PET has a very high sensitivity for the detection of tumor lesions, whereas more ''specialized'' tracers, such as 18 F-DOPA and 18 Fdopamine show only marginal tumoral uptake (21,22). It is important to distinguish between local disease recurrence, which may be surgically curable, and systemic disease, in which case the aim is palliation.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings on other aggressive (dedifferentiated?) neuroendocrine tumors, such as small cell lung cancer and metastatic paraganglioma in patients with a SDHB gene mutation, in which 18 F-FDG PET has a very high sensitivity for the detection of tumor lesions, whereas more ''specialized'' tracers, such as 18 F-DOPA and 18 Fdopamine show only marginal tumoral uptake (21,22). It is important to distinguish between local disease recurrence, which may be surgically curable, and systemic disease, in which case the aim is palliation.…”
Section: Discussionmentioning
confidence: 99%
“…However, FDOPA-PET did not show more lesions than FDG-PET in the two true-positive patients and the contrast of the images was lower. We already observed this lower contrast with FDOPA-PET, as compared with FDG-PET, in small-cell lung cancer, another aggressive tumor of endocrine origin [14]. One potential advantage of FDOPA-PET over FDG-PET is its ability to detect brain metastases of MCC that are rare but should not be overlooked [18].…”
Section: Discussionmentioning
confidence: 97%
“…Becherer et al [15], who recently drew the same conclusion, reported that FDOPA-PET performs better than SRS in a series of 57 neuroendocrine lesions, mostly digestive carcinoid tumors. FDOPA is also taken up by small-cell carcinoma of the lung [14] and by cutaneous melanoma [17], both of which share similarities with MCC. The present case reports demonstrate that FDOPA is also taken up by MCC.…”
Section: Discussionmentioning
confidence: 99%
“…Because this tumor type may express neuroendocrine markers, Jacob et al performed a very small study in 4 patients with small cell lung cancer and compared 18 F-FDG and 18 F-DOPA imaging (54). The performance of 18 F-DOPA was relatively poor compared with that of 18 F-FDG PET and conventional imaging, because FIGURE 10.…”
Section: Miscellaneous Conditionsmentioning
confidence: 99%